Empowering Indonesian Migrant Workers in Taiwan through Stress Management Training - Nohan Arum Romadlona; Sapto Adi; Farah Farida Tantiani; Deslaely Putranti (Universitas Nahdlatul Ulama Surabaya, 2024)
Indonesian Migrant Workers (PMI) face various problems, one of which is mental health problems. PMI in Taiwan were reported to have various mental health problems which have negative consequences. Community service activities are carried out to provide training on the importance of stress management and provide alternative positive coping strategies. The results of the training showed an increase in knowledge of 19.67% regarding stress management from 16 PMI in Taipei, Taiwan. A series of training is also equipped with activity that can help improve mental and physical health. It is hoped that comprehensive activities can be carried out regularly and become a forum for PMI to openly discuss the various problems.